Hubungan Jenis Plasmodium falciparum dan Plasmodium vivax dengan Kejadian Anemia pada Pasien Malaria di RSUD Ratu Aji Putri Botung Penajam Paser Utara: Relationship between Plasmodium falciparum and Plasmodium vivax Types with the Incidence of Anemia in Malaria Patients at Ratu Aji Putri Botung Hospital, Penajam Paser Utara - Doni Suryadi; Vera Madonna Lumban Toruan; Fransiska Anggreni Sihotang; Loly Rotua Dharmanita Siagian (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Malaria is a disease caused by Plasmodium infection that is still a health problem in the tropical area including Indonesia. Penajam Paser Utara is the only district with a high level of malaria endemicity outside eastern of Indonesia which is located at the Province of East Kalimantan. Malaria can cause various complications including haematological abnormalities. Haematological abnormalities that are often found in both falciparum malaria and vivax malaria is anaemia. The purpose of this study was to determine the relationship between the types of Plasmodium falciparum and Plasmodium vivax with the incidence of anaemia in malaria patients at Ratu Aji Putri Botung, Penajam Paser Utara hospital. This research is an observational analytic study with cross sectional method. The data was obtained from medical records of hospitalized malaria patients at Ratu Aji Putri Botung Penajam Paser Utara hospital in the period of January 2013 – August 2018 by purposive sampling method. The data were analyzed using the Chi-square test. The subjects of the study were 310 malaria patients consisting of 60,3% (n=187) patients infected with Plasmodium falciparum and 39,7% (n=123) patients infected with Plasmodium vivax. The majority of research subjects were male (95,8%) and were in the 26 – 40 years age group (56,5%). Anaemia was found in 49% of malaria patients dominated by vivax malaria patients (52%). Statistical test result between types of Plasmodium with the incidence of anaemia was p = 0,391. It was concluded that there was no association between the types of Plasmodium falciparum and Plasmodium vivax with the incidence of anaemia in malaria patients.